Function and Mechanism of RGD in Bone and Cartilage Tissue Engineering - Yang, Meng; Zhang, Zheng-Chu; Liu, Yan; Chen, You-Rong; Deng, Rong-Hui; Zhang, Zi-Ning; Yu, Jia-Kuo; Yuan, Fu-Zhen (Frontiers in Bioengineering and Biotechnology, 2021)
Abstract: Bone and cartilage injury is common, tissue engineered scaffolds are potential means to repair. Because most of the scaffold materials used in bone and cartilage tissue engineering are bio-inert, it is necessary to increase the cellular adhesion ability of during tissue engineering reconstruction. The Arginine - Glycine - Aspartic acid (Arg-Gly-Asp, RGD) peptide family is considered as a specific recognition site for the integrin receptors. Integrin receptors are key regulators of cell-cell and cell-extracellular microenvironment communication. Therefore, the RGD polypeptide families are considered as suitable candidates for treatment of a variety of diseases and for the regeneration of various tissues and organs. Many scaffold material for tissue engineering and has been approved by US Food and Drug Administration (FDA) for human using. The application of RGD peptides in bone and cartilage tissue engineering was reported seldom. Only a few reviews have summarized the applications of RGD peptide with alloy, bone cements, and PCL in bone tissue engineering. Herein, we summarize the application progress of RGD in bone and cartilage tissue engineering, discuss the effects of structure, sequence, concentration, mechanical stimulation, physicochemical stimulation, and time stimulation of RGD peptide on cells differentiation, and introduce the mechanism of RGD peptide through integrin in the field of bone and cartilage tissue engineering.